1997
DOI: 10.1126/science.275.5307.1759
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Parity Nonconservation and an Anapole Moment in Cesium

Abstract: The amplitude of the parity-nonconserving transition between the 6S and 7S states of cesium was precisely measured with the use of a spin-polarized atomic beam. This measurement gives Im(E1pnc)/beta = -1.5935(56) millivolts per centimeter and provides an improved test of the standard model at low energy, including a value for the S parameter of -1.3(3)exp (11)theory. The nuclear spin-dependent contribution was 0.077(11) millivolts per centimeter; this contribution is a manifestation of parity violation in atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
1,149
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,123 publications
(1,223 citation statements)
references
References 29 publications
58
1,149
3
1
Order By: Relevance
“…The first-order Uehling shifts and the breakdown of the core relaxation contributions for the lowest five valence levels of Cs are presented in Table II. In the second column the first-order results δ (1) are given. In the final two columns, the shifts due to core relaxation are presented, divided into the direct and exchange contributions.…”
Section: Core Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-order Uehling shifts and the breakdown of the core relaxation contributions for the lowest five valence levels of Cs are presented in Table II. In the second column the first-order results δ (1) are given. In the final two columns, the shifts due to core relaxation are presented, divided into the direct and exchange contributions.…”
Section: Core Relaxationmentioning
confidence: 99%
“…Obviously, since the Uehling potential acts at a distance close to the nuclear radius, ϕ Br |V Ueh |ϕ Br = c 2 ϕ|V Ueh |ϕ . If the range of the correction to the Hartree-Fock potential δV Ueh HF were within a B , then ϕ Br |V Ueh +δV Ueh HF |ϕ Br = c 2 ϕ|V Ueh +δV Ueh HF |ϕ also, i.e., δ Br = c 2 δ = (δ (1) Br /δ (1) )δ . We do notice some deviation from this relation, which is a result of the long range of the relaxation correction to the HartreeFock potential; this range indeed extends beyond r = a B , as we saw in the previous section.…”
Section: Exp Amentioning
confidence: 99%
“…Given the universality of this PVED, it has been suggested as a possible origin of biological homochirality, although due to its small value, the enantioselection would have taken place through powerful mechanisms of amplification as those involving nonlinear processes in systems far from equilibrium. 4,5 Although the weak interaction has been extensively studied and observed in atoms, 6,7 it has only been predicted in molecules. Electroweak quantum chemistry calculations predict the PVED to be between 10 À13 and 10 À21 eV [8][9][10][11] but no conclusive energy difference has been reported, for instance, in experimental spectroscopic studies of the CHBrClF molecule reaching an energy resolution of about 10 À15 eV.…”
Section: Introductionmentioning
confidence: 99%
“…We are currently working on improving the number of trapped atoms by using a double MOT system and thus having a much longer trap life-time. Radioactive 210 Fr has a lifetime of approximately 3 min which, when contained in a trap, is long enough to perform the sequence of measurements necessary for determining the parity violation signal [21]. With respect to other precision spectroscopy to test discrete symmetries, Romalis and Fortson [24] have shown that to perform a more sensitive test of time invariance with trapped atoms in a dipole trap than presently done, it is necessary to have about 10 8 trapped atoms interrogated for about 10 s.…”
Section: Discussionmentioning
confidence: 99%